(untitled) ("Conference on Universal Science Research 2023", 2023)
The landscape of web development is evolving at an unprecedented pace, driven by technological innovations and changing user demands. This paper provides an in-depth exploration of the future trends in web development and offers actionable insights for beginners eager to embark on this dynamic journey. From emerging technologies like Progressive Web Apps and Artificial Intelligence to essential programming languages and project management tools, this paper equips aspiring developers with a holistic understanding of the evolving web development landscape.